2015
DOI: 10.1101/015966
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The interplay between DNA methylation and sequence divergence in recent human evolution

Abstract: Despite the increasing knowledge about DNA methylation, the understanding of human epigenome evolution is in its infancy. Using whole genome bisulfite sequencing we identified hundreds of differentially methylated regions (DMRs) in humans compared to non-human primates and estimated that ∼25% of these regions were detectable throughout several human tissues. Human DMRs were enriched for specific histone modifications and the majority were located distal to transcription start sites, highlighting the importance… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 48 publications
3
8
0
Order By: Relevance
“…Furthermore, while the DMRs utilized here were obtained from bone samples, the authors of the original study (28) referred to the report by HernandoHerraez et al (40) which demonstrated that species-specific DMRs tend to be conserved across tissues and as such should not represent tissue-specific variations. Other studies also showed that neurological systems were enriched for methylation differences even when the tissue samples analyzed were not neurological (41)(42)(43). Therefore, we believe that our results are valid for a 'brain' phenotype even though the DMRs were derived from non-brain tissues.…”
Section: Discussionsupporting
confidence: 61%
“…Furthermore, while the DMRs utilized here were obtained from bone samples, the authors of the original study (28) referred to the report by HernandoHerraez et al (40) which demonstrated that species-specific DMRs tend to be conserved across tissues and as such should not represent tissue-specific variations. Other studies also showed that neurological systems were enriched for methylation differences even when the tissue samples analyzed were not neurological (41)(42)(43). Therefore, we believe that our results are valid for a 'brain' phenotype even though the DMRs were derived from non-brain tissues.…”
Section: Discussionsupporting
confidence: 61%
“…This trend is robust with respect to the species used to initially locate T-DMRs (Additional File 2: Figures S8-S9). Thus, our results suggest that in general, inter-tissue methylation differences within a species tend to be conserved, consistent with the observations of previous studies [7, 13, 15, 53, 54].…”
Section: Resultssupporting
confidence: 92%
“…We also found a large number of pairwise tissue DMRs and tissue-specific DMRs to be conserved in the three primates we studied. Our observations are qualitatively consistent with those of previous studies that mostly used microarrays to measure methylation levels [7, 13, 41]. However, the high resolution of our sequence-based DMR data allowed us to examine a much larger number of CpG sites.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This study estimated that ~10% of the CGI regions differed significantly between human and chimpanzee. A recent paper was performed with whole-genome bisulphite sequencing (BiS-seq) generating data for ~6 million well-covered CpGs, in peripheral blood across human, chimpanzee, gorilla, and orang-utan [88]. This identified that sDMRs were also enriched for species-specific nucleotide changes and hypomethylated s-DMRs were specifically enriched twofold for endogenous retroviruses (ERVs).…”
Section: Sequence Influence On the Dna Methylomementioning
confidence: 99%